Prognostic Impact of Intracranial Pressure Monitoring in Patients with Severe Traumatic Brain Injury - Borchardt, Bárbara Calistro; Freitas, Luanna Corrêa de Oliveira; Filho, Ademar Milton de Souza; da Rosa, Áurea Maria Soares; Gabe, Milena Bancer; Madeira, Kristian; Moreira, Carlos Fernando dos Santos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Objectives The aim of the present study was to analyze the prognostic impact of intracranial pressure (ICP) monitoring in patients with severe traumatic brain injury (TBI).Methods An observational, retrospective and quantitative study was performed. The sample consisted of 246 patients diagnosed with severe TBI, from January 2009 to August 2017.Results Out of the total sample, 43.56% of the patients were submitted to ICP monitoring. The mean time of use of the catheter was 1.7 days. In both groups, males were the most affected, and the majority of the patients were < 50 years old. Automobile accident was the main etiology of TBI. In the initial clinical evaluation, mydriatic pupils were related to death and normal pupil reaction at hospital discharge. The monitored group performed a larger number of computed tomography (CT) scans, with a mean of 2.6 examinations, with cerebral edema being the most common finding. Regarding the prognosis, those who used a catheter for ICP monitoring had a 47% reduction in the chance of death when compared with those who did not use the catheter. The stay duration both in the hospital and in the intensive care units was higher in patients who underwent ICP monitoring; periods > 30 days were related to meningitis, especially in those who used the catheter.Conclusion Patients who used a catheter for ICP monitoring had a significant improvement in survival.
Keywords: traumatic brain injury; intracranial pressure; prognosis